2015
DOI: 10.2139/ssrn.2603597
|View full text |Cite
|
Sign up to set email alerts
|

The Pan-European Population Distribution Across Consistently Defined Functional Urban Areas

Abstract: We analyze the first data set on consistently defined functional urban areas in Europe and compare the European to the US urban system. City sizes in Europe do not follow a power law: the largest cities are "too small" to follow Zipf's law.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
8
0

Year Published

2018
2018
2022
2022

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(8 citation statements)
references
References 7 publications
0
8
0
Order By: Relevance
“…FUAs have the advantage of at least partially overcoming a list of problems associated with de jure spatial units (Stimson 2016) and to maximise comparability across countries and jurisdictions. FUAs have been used in several studies analysing different issues of urban development, including city size distribution (Schmidheiny and Suedekum 2015;Veneri 2016), urban spatial structure (Veneri 2018;OECD 2018), or agglomeration economies (Ahrend et al 2017), among others.…”
Section: Data and Stylized Factsmentioning
confidence: 99%
“…FUAs have the advantage of at least partially overcoming a list of problems associated with de jure spatial units (Stimson 2016) and to maximise comparability across countries and jurisdictions. FUAs have been used in several studies analysing different issues of urban development, including city size distribution (Schmidheiny and Suedekum 2015;Veneri 2016), urban spatial structure (Veneri 2018;OECD 2018), or agglomeration economies (Ahrend et al 2017), among others.…”
Section: Data and Stylized Factsmentioning
confidence: 99%
“…Another major support in favor of Zipf's law comes from the studies who argue that a proper definition of the city should be used. This literature shows that empirical validation of Zipf's law is sensitive to the definition of cities [12,14,19,36,37,63,[108][109][110][111][112]. Though different authors have used different words to define overall the literature has used three types of city definitions: administratively defined cities [14], functionally defined cities [19,37,111,112] and natural cities [36,109,110].…”
Section: Definition Of a City And Zipf's Lawmentioning
confidence: 99%
“…This literature shows that empirical validation of Zipf's law is sensitive to the definition of cities [12,14,19,36,37,63,[108][109][110][111][112]. Though different authors have used different words to define overall the literature has used three types of city definitions: administratively defined cities [14], functionally defined cities [19,37,111,112] and natural cities [36,109,110]. This literature has shown that Zipf's law offers a better fit to city size distribution when cities are defined as functionally defined urban areas rather than the administratively defined cities, and a pure form of Zipf's law is observed if the cities are measured as natural cites.…”
Section: Definition Of a City And Zipf's Lawmentioning
confidence: 99%
See 2 more Smart Citations